Online as the New Frontline: Affect, Gender, and ISIS-Take-Down on Social Media - Elizabeth Pearson (Studies in Conflict & Terrorism, 2017)
Using a dataset of more than 80 accounts during 2015, this article explores the gendered ways in which self-proclaiming Twitter Islamic State of Iraq and Syria (ISIS) supporters construct community around “suspension.” The article argues that suspension is an integral event in the online lives of ISIS supporters, which is reproduced in online identities. The highly gendered roles of ISIS males and females frame responses to suspension, enforcing norms that benefit the group: the shaming of men into battle and policing of women into modesty. Both male and female members of “Wilayat Twitter” regard online as a frontline, with suspension an act of war against the “baqiya family.” The findings have implications for broader repressive measures against ISIS online.